Penerapan Konseling Individu Berbasis Islam Untuk Mengurangi Perilaku Biseksual (Studi Kasus Pada Klien “H” Di Kota Palembang) - Ersya Septiani; Zhila Jannati; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "Application of Islamic-Based Individual Counseling to Reduce Bisexual Behavior (Case Study of "H" Clients in Palembang City)". Client "H" fell into bisexual behavior due to sexual harassment. This research aims to find out how bisexual behavior is described in client "H" before the application of Islamic-based individual counseling, to find out how to apply Islamic-based individual counseling to reduce bisexual behavior and also to find out what the picture of bisexual behavior in client "H" is after the implementation of individual-based counseling. Islam. This research uses a qualitative approach with a case study research method. The data collection techniques used are observation, interviews and documentation. The research subject is client "H". The results of this research show that client "H" has experienced changes where client "H" only has an interest in women, has a stable heterosexual relationship and no longer has a homosexual relationship, feels uncomfortable having romantic or sexual relationships with both genders so that Client "H" only feels comfortable having relationships with women, and has never changed sexually between heterosexual and homosexual.